Caracterização ambiental e condição do uso da terra da paisagem do município de São Félix do Araguaia - MT - Alves, Marilene de Moura (Universidade Federal de São Carlos, 2009)
There is an increase need for remote sensing data and associated analysis techniques in detecting and monitoring landscape change, particularly for resource management and planning. Information derived from remote sensing spatial data landscape has often been used to assist in the formulation of policies and provide insight into land-use patterns. To understanding human disturbance regimes for developing conservation and ecosystem management plan and for targeting ecological areas that define scarce ecosystems services this study has provided a landscape structure digital database at scales of observations that meet various mapping criteria (geology, geomorphology, pedology, hydrography, hypsometry, road net, settlements, legally protected areas and land-use of the São Félix Araguaia municipality. The monitoring current land-use for characterizing anthropogenic and natural surfaces was based on the use of the Systems of Geographical Information and image LandSat 5 TM. The pattern of land-use reflects the outcomes of more than one human process; for instance, cropland, pastureland and settlements expansion. Natural vegetation was the most abundant land use type, occupying 63.20% of the municipal district total area. Following forest, crop was the next most abundant land use type with 34.75% of the total area. The urban area value is incipient (0.76% of the total area), evidencing that the landscape changes are not influenced by the urban growth. In spite of the amount of forested areas in the municipality is important to point out that many of them are fragmented, isolated, or very close to areas in that the agriculture is the predominant activity. Regional and municipal planners require up-to-date information related to a digital database to effectively manage land development and plan for change.
Environmental characterization and land-use condition of the landscape of São Félix do Araguaia municipality
Keywords: Análise e planejamento ambiental; Solo - uso; Zoneamento ambiental; Sistemas de informação geográfica; Estrutura da paisagem; SIG; Landscape structure; Land use; Environmental zoning; GIS; CIENCIAS BIOLOGICAS::ECOLOGIA